(untitled) (Jurnal Legislatif, 2021)
Abstract Insider trading is a form of trading that is prohibited in securities transactions in the capital market. The practice of insider trading is a violation of the principle of openness which is the soul of the capital market industry. The problem to be answered through this research is related to the problem of insider trading crimes and solutions in realizing protection and legal certainty for investors in Indonesia. This study uses a normative juridical approach. The results of this research are that in order for the capital market in Indonesia to run optimally and be able to bring benefits to the economy in Indonesia, crimes in the capital market such as insider trading must be resolved through a legal process. Therefore, rules, settlement systems, and law enforcement are needed in solving the problems of insider trading in the capital market in Indonesia. Keywords: Capital market; Insider trading; Legal protection; Legal certainty Abstrak Insider trading atau perdagangan orang dalam merupakan bentuk perdagangan yang dilarang di dalam transaksi efek di pasar modal. Praktik insider trading merupakan bentuk pelanggaran terhadap prinsip keterbukaan yang merupakan jiwa dari industri pasar modal. Permasalahan yang ingin dijawab melalui penelitian ini adalah terkait problematika kejahatan insider trading dan solusi dalam mewujudkan perlindungan dan kepastian hukum bagi para investor di Indonesia. Penelitian ini menggunakan pendekatan yuridis normatif. Adapun hasil dari penelitian ini adalah agar pasar modal di Indonesia dapat berjalan secara maksimal dan dapat mendatangkan keuntungan perekonomian di Indonesia maka kejahatan di pasar modal seperti insider trading harus dapat diselesaikan melalui proses hukum. Oleh karena itu, diperlukan aturan, sistem penyelesaian, dan penegakan hukum dalam penyelesaian problematika tindak insider trading dalam pasar modal di Indonesia. Kata Kunci: Insider Trading; Kepastian Hukum; Pasar Modal; Perlindungan Hukum.